2009
DOI: 10.1373/clinchem.2008.115808
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Methylated SEPT9 DNA in Plasma Is a Biomarker for Colorectal Cancer

Abstract: BACKGROUND:The presence of aberrantly methylated SEPT9 DNA in plasma is highly correlated with the occurrence of colorectal cancer. We report the development of a new SEPT9 biomarker assay and its validation in case-control studies. The development of such a minimally invasive blood-based test may help to reduce the current gap in screening coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
266
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(293 citation statements)
references
References 23 publications
(36 reference statements)
12
266
1
9
Order By: Relevance
“…Likewise, septin 9 (SEPT9), is a hypermethylation biomarker for CRC. In a blinded study the SEPT9 plasma assay showed a sensitivity of 67% and specificity of 89% for detection of colorectal cancer (deVos et al 2009, Tanzer et al 2010. Based on preclinical data from such studies, the PRESEPT trial, a prospective, population-based study to determine the clinical performance of SEPT9 for colorectal cancer screening of guideline-eligible individuals, opened in 2009 and closed recently with publication of results anticipated in the near future.…”
Section: Dna Methylation Biomarkers For Cancer Detection and Tumor Prmentioning
confidence: 99%
“…Likewise, septin 9 (SEPT9), is a hypermethylation biomarker for CRC. In a blinded study the SEPT9 plasma assay showed a sensitivity of 67% and specificity of 89% for detection of colorectal cancer (deVos et al 2009, Tanzer et al 2010. Based on preclinical data from such studies, the PRESEPT trial, a prospective, population-based study to determine the clinical performance of SEPT9 for colorectal cancer screening of guideline-eligible individuals, opened in 2009 and closed recently with publication of results anticipated in the near future.…”
Section: Dna Methylation Biomarkers For Cancer Detection and Tumor Prmentioning
confidence: 99%
“…Several septins have been identified as mixed lineage leukemia (MLL) fusion partners that contribute to the pathogenesis of leukemia (Borkhardt et al, 2001;Cerveira et al, 2006;Kojima et al, 2004;Osaka et al, 1999). Notably, septins are also being used in a diagnostic context, with the methylation of the SEPT9 promoter serving as an effective biomarker for colorectal cancer (deVos et al, 2009;Grutzmann et al, 2008;Lofton-Day et al, 2008). The role of septins in neurological disorders and cancer is complex and poorly understood.…”
Section: Septin-associated Diseasesmentioning
confidence: 99%
“…Most recently, serum metabolites have been studied to be used as potential biomarkers for early CRC detection [13]. Some important biomarkers characteristic of early CRC development such as methylated Septin 9 (SEPT9) and miRNA-21 have been reported [14,15]. These experimental screening techniques, though promising to provide potential markers for early CRC diagnosis, still require further validation in population-based studies [16].…”
Section: Introductionmentioning
confidence: 99%